The Effect of Compensation and Work Environment on Job Performance through Job Satisfaction (Case Study at PT IndoPersonnel - Hadi Kuncoro, Ambrosius Purwadi; Wibowo, Imam; Latukismo, Tatag Herbayu (Journal of Islamic Studies & Social Science, 2025)
This study aims to analyze the effect of compensation and work environment on employee performance through job satisfaction as a mediating variable at PT IndoPersonnel. The research is based on the issue of employee performance not consistently meeting company targets in recent years, which is suspected to be caused by both internal and external factors such as an uneven compensation system and suboptimal working conditions. The focus is to examine how compensation and the work environment influence job satisfaction, and how job satisfaction, in turn, improves employee performance. This study employs a quantitative approach with an explanatory type and causal design. The population consists of operational employees of PT IndoPersonnel, with a sample of 54 respondents including checkers, operators, and laborers. Data were collected through questionnaires. The collected data were analyzed using path analysis to determine both direct and indirect relationships among the variables. Instrument tests were conducted to assess the validity and reliability of the data, and classical assumption tests were applied to ensure the robustness of the model.The results indicate that compensation and the work environment have a positive and significant effect on job satisfaction. Job satisfaction also has a positive and significant influence on employee performance. Furthermore, compensation and the work environment indirectly affect performance through job satisfaction. These findings suggest that improving compensation and working conditions will enhance job satisfaction, which ultimately contributes to improved employee performance.